Improvement of public management mechanisms in the direction of countering hybrid threats to national security - Bielai, Serhii; Emanov, Vladislav; Trobiuk, Volodymyr; Sporyshev, Kostiantyn; Petik, Andrii (Edelweiss Applied Science and Technology, 2024)
The article represents an attempt of conceptual comprehension of the phenomenon of hybrid threats, which, although inextricably linked with hybrid warfare, still may not include armed conflict even with participation of only irregular combatants. Rather, hybrid threats are aimed at undermining adversary’ infrastructure or gaining much control over it, and sow internal societal tension. Geopolitical components, drivers and factors of hybrid threats are analyzed. Based on analysis of literature sources and practical cases, it is concluded that anticipatory approach is the only way of effective combatting hybrid threats, but implementation of this approach could be backed by a collective change in mentality and a stronger national narrative, while the initiative should be suggested by public administration. There is a need for fresh thinking while expanding the traditional enemy-centric threat assessment and response.